DAMPAK PENCEMARAN LINGKUNGAN AKIBAT LIMBAH INDUSTRI PENGOLAHAN IKAN DI MUNCAR (Studi Kasus Kawasan Industri Pengolahan Ikan di Muncar – Banyuwangi) - Setiyono, Setiyono; Yudo, Satmoko (Center for Environmental Technology, 2008)
Muncar area is a regional fish producer. There, we can find big and small scale fish processing industries and even home industries. Those industry produce on the average 1,300 ton/day processed fish. Production activities caused environmental pollution, especially air, water and soil pollution. Source of this pollution are from transportation movement and developmnet of raw material, quality control activities to employeeÃ¢â‚¬â„¢s activities (domestic waste). Right now the process of waste management is so little and peopleÃ¢â‚¬â„¢s understanding about wastewater treatment (IPAL) and waste management system is so limited. Almost all waste from this area is flowed away to the public canal. Flowing away waste directly without any process could increase environmental pollution around industrial location. This paper explains how big the potential waste water pollution, kind and charactestic of pollution from fish processing industries and doing waste management evaluation in fish processing indutries in Muncar. Italso shows sort of pollution effect as a result of disposing fish processing industry waste in Muncar. Ã‚Â Ã‚Â Kata Kunci : Industri Pengolahan Ikan, Dampak Pencemaran Limbah Industri.